Analisis Respons Fisiologis melalui Indikator Waktu Pemulihan dan Saturasi Oksigen pada Atlet Pencak Silat Berbasis Sistem Pemantauan Terintegrasi - Gatot Margisal Utomo; Muhammad Wahyono; Ismawandi Bripandika Putra (MAN Insan Cendekia Jambi, 2026)
This study aimed to analyze the physiological responses of pencak silat athletes through the indicators of recovery time and oxygen saturation (SpO₂) using an integrated physiological monitoring system. A quasi-experimental pretest–posttest design was employed with 30 athletes as participants. Each athlete followed a controlled high-intensity training program while physiological data were collected in real-time to assess bodily adaptation to training load. Results showed a significant reduction in recovery time from an average of 183 ± 15 seconds to 152 ± 12 seconds, alongside a stable increase in SpO₂ from 96 ± 1.2% to 97 ± 1%. These findings indicate that high-intensity training with physiological monitoring can improve cardiac recovery efficiency and maintain oxygenation stability. The study highlights the importance of individualized training programs based on real-time data to optimize athlete performance and minimize overtraining risks. In conclusion, the integrated monitoring system is effective in measuring physiological adaptation of pencak silat athletes to high-intensity training programs, providing a scientific basis for more personalized and data-driven training strategies.